2017
DOI: 10.15171/bi.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension in human pathophysiology and its application as a medical diagnostic tool

Abstract: Introduction: Pathological features of disease appear to be quite different. Despite this diversity, the common feature of various disorders underlies physicochemical and biochemical factors such as surface tension. Human biological fluids comprise various proteins and phospholipids which are capable of adsorption at fluid interfaces and play a vital role in the physiological function of human organs. Surface tension of body fluids correlates directly to the development of pathological states. Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 89 publications
(125 reference statements)
1
32
0
Order By: Relevance
“…This suggests that the surface tension gradient that exists between the alveolar and tracheobronchial mucus may be due, in part, to increasing resistance to surfactant mobility of the more viscoelastic mucus of the conducting airways. As a number of diseases that affect the conducting airways have been linked to changes in surface tension 14 , a better understanding of this surface tension behavior of lung surfactant could facilitate lung disease diagnosis and treatment. Further, the higher surface tensions and reduced surfactant transport associated with viscoelastic subphases may play a crucial role in the barrier function of tracheobronchial mucus, serving to reduce the ability of microorganisms and deposited aerosols to penetrate into the mucus or transport laterally across the surface.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the surface tension gradient that exists between the alveolar and tracheobronchial mucus may be due, in part, to increasing resistance to surfactant mobility of the more viscoelastic mucus of the conducting airways. As a number of diseases that affect the conducting airways have been linked to changes in surface tension 14 , a better understanding of this surface tension behavior of lung surfactant could facilitate lung disease diagnosis and treatment. Further, the higher surface tensions and reduced surfactant transport associated with viscoelastic subphases may play a crucial role in the barrier function of tracheobronchial mucus, serving to reduce the ability of microorganisms and deposited aerosols to penetrate into the mucus or transport laterally across the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The g is more accurate and continuous predictor of protenuria. g of biological liquid may depend on age and sex, but more under some physiological conditions such as menstrual period and various diseases 3 . In this study it is observed that excretion of large amount of albumin through urine lowers the g of CKD urine.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship may be used to identify the major proteins present in the fluid from an ovarian cyst. The change in g is responsible for bubble formation in urine, which can be attributed to kidney disease and changes in Physiological condition of body 3 . The g of urine and effect of bile salts, protein, and temperature and storage time has been investigated 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Human biological fluids contain numerous surfactants that help maintain essential functions of various tissues and organs by controlling the surface tension of human tissue and organ interfaces, and altered surface tension is a characteristic of some diseases . Pulmonary surfactants can be secreted by alveolar type II epithelial cells and maintain very low surface tension of the lung at the end of expiration for efficient gas exchange.…”
Section: Introductionmentioning
confidence: 99%